Customer perception on service quality towards tourism customer satisfaction in Malaysian marine tourism sector - Ulfy, Mohammad Arije; Hossin, Md Suliman; Karim, Md Wasiul; Suib, Fatin Husna (Editura Universitati din Oradea, 2021)
Marine based tourism has emerged as a subject of concern in the area of ocean and coastal management. Today, demand for marine tourism has increased dramatically and is highlighted as one of the new horizons and fastest-growing sectors in the world’s tourism industry. Malaysia is indeed one of the countries with the most beautiful and diversified marine life. The fundamental purpose of this study is to examine the satisfaction of tourists towards the service quality of marine tourism in Malaysia. The development of the research framework is based on the SERVQUAL model. A total of 300 responses were received from the Klang Valley area of Malaysia. For the purpose of processing and analyzing the data, Partial Least Square (PLS-SEM) method was employed. By applying a two-step approach, the study assesses the measurement model and the structural model. Findings from the survey reveal that assurance, tangibility, empathy, reliability, and responsiveness have a significant positive relationship with customer satisfaction thus these factors describe customer satisfaction adequately. This study would enable policymakers and tourism companies to develop policies to improve customer satisfaction by increasing the quality of service